A qualitative inquiry into the accrual process of entrepreneurs’ social capital through their use of social media. - Yaqzan, Syed (Cranfield University, 2022)
Aim: To explore the accrual process of entrepreneurs’ social capital through their use of social media. Method: This study adopts a critical realist ontological position and applies a multi-method approach. Empirical data for the study is collected from 35 semi-structured interviews conducted with entrepreneurs in Pakistan. The qualitative data from the interviews was analysed using the Gioia methodology (Gioia et al., 2010). To triangulate the data and to bring additional rigor to the findings, netnography (Kozinets, 2015) was used to collect real-time data from the social media accounts (Facebook and LinkedIn) of respondents for a period of four months after the interviews. Findings: This study identified two key potential antecedents of accrual process of entrepreneur’s social capital that may influence their user behaviour: “privacy concerns” and “context of audiences”. The relationship between the two potential antecedents, privacy concerns and user behaviour, is likely moderated by the context of the audience on social media. If the audience is “targeted” (i.e., the entrepreneurs are aware of who the audience is), they will likely opt for a higher degree of self-presentation, self-disclosure, thereby positively influencing the accrual of social capital. Furthermore, this research finds that in the online context, large and diverse networks of entrepreneurs tend to comprise collapsed audiences. This is likely to limit the expressive behaviour of entrepreneurs, which possibly limit the overall accrual process of social capital in social media. Hence, a large and diverse online network may become a “vanity fair”, with limited mobility of resources between the connections. Moreover, this research highlights the difference between entrepreneurs’ reported privacy concerns and their actual user behaviour to protect their privacy online. Although, participants reported interest in protecting their privacy and maintaining a positive attitude towards privacy-protection behaviour during the interviews. But the findings from the netnography suggested that this reported interest rarely translates into actual privacy- protective behaviour. Finally, this research underlines the importance of "engagement with others' content" in social media for the accrual of bridging social capital. Such engagement with others in public plays a role of "reaching out to new people" by publicly engaging with others' content; likely help generate visibility for entrepreneurs to ties outside their network. Hence, the findings of the study may help entrepreneurs connect with weak ties which are source of bridging social capital. Avenues for future research: This research paves the way for a better understanding of the interplay of entrepreneurs' social capital online and offline. Do network development and management efforts that include offline and online social networks foster the accrual of social capital for entrepreneurs? The second avenue for the future research may pursue an in-depth understanding of the social capital accrual on different social networking platforms. For example, do interplay between antecedents is different on Facebook or LinkedIn than Instagram and Twitter?
Koryak, Oksana - Associate Supervisor
Keywords: social media; Social Capital; Entrepreneurs; Accrual Process